Mastering responsive web design with HTML5 and CSS3 : become a master in RWD with this practical and engaging guide - Zea, Ricardo (Community experience distilled., 2015)
Push your HTML and CSS skills to the limit and build professional grade, responsive websites About This Book Take your RWD skills to the next level with HTML5 and CSS3 best practices that will give you a solid foundation to build out from Harness the power of the CSS pre-processor Sass to speed up the creation of your CSS Each chapter dives deep in to different aspects of RWD and is designed to get you up to speed with the latest developments in professional web design Who This Book Is For If you're already building responsive designs and are looking to level up your skills, then Mastering Responsive Web Design is the book for you. Regardless of whether you're a web designer, or web developer, you'll find something here to help you in your responsive design journey. What You Will Learn Install and use Sass with SCSS syntax to create your CSS Use HTML5 tags the right way, for the right type of content Enhance the experience of users with assistive technology with ARIA roles Design with a desktop-first approach, but implement with mobile-first methodology Master your layouts by creating your own scalable CSS grid, or using Flexbox for total layout?flexibility' Retrofit your old web sites with your new responsive design skills Deal with legacy browsers, and learn how to keep your designs consistent Implement widely used responsive patterns, such as the?drawer navigation?, the?off-canvas? and the?flexbox-based? navigation patterns Find the best way to serve the right type of image and how to make videos responsive Build custom responsive emails to ensure the message gets across regardless of the device In Detail Building powerful and accessible websites and apps using HTML5 and CSS3 is a must if we want to create memorable experiences for our users. In the ever-changing world of web design and development, being proficient in responsive web design is no longer an option: it is mandatory. Each chapter will take you one step closer to becoming an expert in RWD. Right from the start your skills will be pushed as we introduce you to the power of Sass, the CSS preprocessor, to increase the speed of writing repetitive CSS tasks. We'll then use simple but meaningful HTML examples, and add ARIA roles to increase accessibility. We'll also cover when desktop-first or mobile-first approaches are ideal, and strategies to implement a mobile-first approach in your HTML builds. After this we will learn how to use an easily scalable CSS grid or, if you prefer ...